Pengembangan media pembelajaran BIPA tingkat dasar berbasis web - Alfarabi Maulana; Indrya Mulyaningsih; Itaristanti Itaristanti (Jurnal Bahasa Indonesia bagi Penutur Asing, 2022)
This research aims to develop a product in the form of a prototype of a basic web-based BIPA learning media. This study uses the Borg & Gall research and development (R&D) method which is limited to the revision stage based on expert assessment. The steps used in this research are 1) potentials and problems; 2) data collection; 3) product design; 4) design validation; and 5) design revision. Based on these five steps, research activities will be divided into two major stages, namely the preliminary stage and the design stage. The data used in the preliminary stage is a word or sentence sourced from some literature as well as videos related to potential and problems that occur in the BIPA learning program. The data used in the product design stage is the results of the preliminary stage and expert assessment of product design. The results of this study are in the form of BIPA learning web products with the status that the product is considered a prototype ready for limited trials. This study concluded that the web-based basic-level BIPA learning media product prototype was declared feasible (within a limited scope) with a feasibility level of 71.52%